Cardiovascular Consequences of Acute Kidney Injury: Treatment Options - Julija G. Voicehovska; Dace Trumpika; Vladimirs V. Voicehovskis; Eva Bormane; Inara Bušmane; Anda Grigane; Eva Moreino; Aivars Lejnieks (Biomedicines, 2023)
Soon after haemodialysis was introduced into clinical practice, a high risk of cardiac death was noted in end-stage renal disease. However, only in the last decade has it become clear that any renal injury, acute or chronic, is associated with high overall and cardiovascular lethality. The need for early recognition of kidney damage in cardiovascular pathology to assess risk and develop tactics for patient management contributed to the emergence of the concept of the “cardiorenal syndrome” (CRS). CRS is a pathophysiological disorder of the heart and kidneys in which acute or chronic dysfunction of one of these organs leads to acute or chronic dysfunction of the other. The beneficial effect of ultrafiltration as a component of renal replacement therapy (RRT) is due to the elimination of hyperhydration, which ultimately affects the improvement in cardiac contractile function. This review considers the theoretical background, current status of CRS, and future potential of RRT, focusing on the benefits of ultrafiltration as a therapeutic option.